A systematic review and mapping of the literature of virtual reality studies in earth science engineering education - Özcan Özyurt; Nergiz Ercil Cagiltay; Hacer Özyurt; Aykut Akgun (Journal of Pedagogical Research, 2021)
Today, earth sciences engineering education programs face with serious problems. It is often not possible to provide experience on different geographical environments or materials. Considering these problems of earth science related engineering education programs, virtual reality environment potentially can provide technology enhanced training alternatives. However, in the literature there are not many studies showing how virtual reality can enhance the earth science related engineering education programs. Accordingly, the aim of this mapping of the literature and systematic review study is to explore studies dealing with virtual reality in the earth sciences engineering education programs. Through a rigorous screening process, the first search in the Scopus database provided 150 studies, where 19 of them were selected in the course of this study and the mapping of the literature report was drawn with all these articles. Additionally, with seven of these articles a systematic review is conducted. The mapping of the literature report shows that studies on this topic have increased in recent years and have been published in a variety of journals. The number of China and USA origins studies are remarkable among the examined studies, which are predominantly in the fields of mining engineering and geological engineering. As a result of the in-depth analyses, the systematic review report indicates that virtual reality applications in the earth sciences engineering education positively contribute to the learning outcomes and experiences of students/trainees from different perspectives.